Cardiovascular Responses to Simultaneous Diving and Muscle Metaboreflex Activation - Di Giacomo, Annalisa; Ghiani, Giovanna Maria; Todde, Francesco; Tocco, Filippo (Frontiers in Physiology, 2021)
Background: The aim of study was to assess hemodynamic changes during simultaneous activation of muscle metaboreflex (MM) and diving reflex (DR) in a laboratory setting. We hypothesized that as long as the exercise intensity is mild DR can overwhelm the MM. Methods: 10 trained divers underwent the following protocol randomly assigned. A) Post-exercise muscle ischemia session (PEMI): 3 min of resting followed by 3 min of handgrip at 30% of maximum force, followed immediately by 3 min of PEMI on the same arm induced by inflating a sphygmomanometer. 3 minutes of recovery was further allowed after the cuff was deflated, for a total of 6 minutes of recovery. B) Control exercise recovery session (CER): the same rest-exercise protocol used for A followed by 6 min of recovery without inflation. C) DR session: the same rest-exercise protocol used for A followed by 1 min of breath-hold (BH) with face immersion in cold water. D) PEMI-DR session: the same protocol used for A with 60 seconds of BH with face immersion in cold water during the first minute of PEMI. Stroke volume (SV), heart rate (HR) and cardiac output (CO) were collected by means of impedance method. Results: At the end of apnea HR was decreased in condition C and D respect to A (-40.8% and -40.3% vs. -9.1%; p<0.05). Since SV increased was less pronounced at the same time point (C=+32.4% and D=+21.7% vs. A=+6.0; p<0.05) thus CO significantly decreased during C and D with respect to A (-23% and -29.0% vs.-1.4% respectively; p<0.05). Conclusion: Results addressed to the hypothesis that DR overcame the MM in our setting.